Assembly of Large Purely Inorganic Ce‐Stabilized/Bridged Selenotungstates: From Nanoclusters to Layers. Issue 5 (25th February 2015) - Chen, Wei‐Chao; Qin, Chao; Li, Yang‐Guang; Zang, Hong‐Ying; Shao, Kui‐Zhan; Su, Zhong‐Min; Wang, En‐Bo
Abstract A versatile one‐pot strategy was used to synthesize two large, purely inorganic selenotungstates, nanocluster K6Na16[Ce6Se6W67O230(OH)6(H2O)17]⋅47 H2O (1) and layer K9Na5Ce(H2O)4[Ce6Se10W51O187(OH)7(H2O)18]⋅45 H2O (2), by combining cerium centers and SeO32− heteroanion templates. Compound 1 displays a Ce‐stabilized hexameric nanocluster with one rhombus‐like {W4O15(OH)3} unit in the center, whereas compound 2 is the first example of a Ce‐bridged layer selenotungstate network based on linkage of the unusual {Ce6Se10W51O187(OH)7(H2O)18} clusters and additional Ce(H2O)4 fragments via Ce‐O‐Se bridges. The compounds were characterized by elemental analyses, IR spectroscopy, thermogravimetric analyses, powder and single‐crystal X‐ray diffraction, and electrospray ionization mass spectrometry. Moreover, the electrochemical property of compound 1 was also investigated.